2016
DOI: 10.4103/2303-9027.180476
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound versus magnetic resonance cholangiopancreatography in suspected choledocholithiasis: A systematic review

Abstract: Background and Objectives:There is a lack of consensus about the optimal noninvasive strategy for patients with suspected choledocholithiasis. Two previous systematic reviews used different methodologies not based on pretest probabilities that demonstrated no statistically significant difference between Endoscopic ultrasound (EUS) and magnetic resonance cholangiopancreatography (MRCP) for the detection of choledocholithiasis. In this article, we made a comparison of the diagnostic ability of EUS and MRCP to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 23 publications
(42 reference statements)
1
24
0
4
Order By: Relevance
“…We commonly employ transabdominal ultrasound for preoperative evaluation in our center and only a few patients had MRCP done preoperatively. While a number of studies (20,21) have affirmed the superiority of MRCP and endoscopic ultrasound for the detection of CBD stones, the cost and availability of these techniques in our setting has limited us to transabdominal ultrasound in most instances. In this study, detection rate of CBD stones with transabdominal USS was 70% with a number of patients only detected intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…We commonly employ transabdominal ultrasound for preoperative evaluation in our center and only a few patients had MRCP done preoperatively. While a number of studies (20,21) have affirmed the superiority of MRCP and endoscopic ultrasound for the detection of CBD stones, the cost and availability of these techniques in our setting has limited us to transabdominal ultrasound in most instances. In this study, detection rate of CBD stones with transabdominal USS was 70% with a number of patients only detected intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients suspected of acute biliary obstruction require diagnostic evaluation even after the presence of gallstone disease has been established using ultrasound. Several trials demonstrated comparable performance of MRCP to endoscopic ultrasound in detection of choledocholithiasis, and this performance drives the cost‐effectiveness of MRCP/MRI as a standard diagnostic approach to suspected acute biliary obstruction, particularly when endoscopic ultrasound may not be readily available …”
Section: Incorporation Of Currently Available Tests Into Potential Nementioning
confidence: 95%
“…Von [268], während ein weiteres systematisches Review acht vergleichende Studien analysierte und für gleiche Prätest-Wahrscheinlichkeiten eine höhere Nachweis-und Ausschluss-Wahrscheinlichkeit der Endosonografie für das Vorliegen einer Choledocholithiasis ermittelte [309]. In einer prospektiv kontrollierten Studie wurde auch über eine tendenziell höhere Spezifität der Endosonografie (95 %) im Vergleich zur MRCP (73 %) berichtet [256].…”
Section: Kommentarunclassified